Partnership and Coalition Efforts for Community-based Research: Towards A Liveable Urban and Rural Settlement in KwaZulu-Natal - Ngcobo, Sibongile A; Khalema, Nene E; Makusha, Tawanda (CSID Journal of Infrastructure Development, 2024)
This paper examines the role of community partnerships and coalitions in the intricate and constantly evolving dynamics of communities in KwaZulu-Natal, South Africa. Various aspects of the community context, such as socioeconomic conditions, geography, environmental factors, demographics, community politics, and cultural norms, often influence these community partnerships and coalitions. This study adopted the Community Coalition Action Theory as an organisational framework to examine the efforts of coalitions and partnerships in community-based research. The research applied a mixed-methods approach. This included a survey and individual interviews within the research organisation responsible for multiple community-based projects in rural and urban areas of KwaZulu-Natal, as well as in-depth interviews with project beneficiaries and senior government officials. An interpretative phenomenological analysis was applied to explore how contextual factors impacted partnership and coalition formation. Our results highlight the importance of community-based partnerships and coalitions in facilitating effective research initiatives that improve the quality of life in rural and urban communities. This study emphasises the importance of incorporating community voices into decision-making processes that impact their lives. Our findings provide insights into how partnership and coalition efforts shape the research process and why they are crucial for community-based research. The results also identify the types of partnerships required for successful research, community planning, and intervention implementation, along with the foundational principles and components needed for effective partnering. This paper advocates for strategic collaborations between academic institutions, government departments, and local communities. It highlights the critical influence of community politics, historical context, and cultural values during the research implementation phase. These findings offer guidance for improving approaches to community-based research implementation, ensuring that research comprehensively addresses the needs of rural and urban communities.